Does the use of a light shot put modify the throwing pattern of elite athletes? - Dinu, D.; Natta, F.; Huiban, C.; Houel, N. (Procedia Engineering, 2014)
The aim of this study is to analyse the influence of the weight mass (6 vs 7.26 kg) in kinematics parameters on an expert throwing shot put in rotation, in order to estimate the influence of using a lighter weight to minimise the arm thrower's risk of injury or during recovery training. This study was done on a sample selection of three elite throwers (best performance 16.51 ± 0,81m) from the French national team, who performed three throws with a 6 Kg weight mass and three others with a 7.26 Kg weight mass. Motion analysis of each throw were recorded using an optoelectronic system (Vicon612) composed of six infrared camcorders and a 3-D modelling of the throwing movement was processed according to the Dapena method. The thrower and weight center of mass velocities were computed for each throwing phase. Friedman Anova analysis showed no significant difference on the subject center of mass and weight velocities (respectively p = 0.86 and p = 0.45) between both weight mass conditions. No significant shot put mass effect, (p = 0.86) on the phases duration in both conditions of weight (6 vs 7.2 kg), were observed. These results suggest that a weight mass lower than 27% could be used for elite athletes training without a change in velocity of the motion throw. This could be used in order to narrow musculo-squeletal overwork and injury during intensive phases of training and/or to quickly return to specific throwing motion during recovery of the shoulder complex. This should allow for the use of a lighter discus during high level training without kinematical alteration of throwing.